(untitled) (Biological Sciences - PJSIR, 2020)
Monotheca buxifolia is an ethno-medicinally important plant of Pak-Afghan regions. The pharmacognostic standards of fruit, leaf, seed, barks of stem and root were set in present study. Microscopy revealed characteristic distinguishable powder drug fragments. Each part showed certain unique florescence behaviour with various reagents under light of various wavelengths. It has a broad spectrum phytochemical profile including amino acids and proteins, fats (fixed oils), sugars (both non reducing and reducing), alkaloids, flavonoids, glycosides, tannins, triterpenoids, phenolics, saponins, phytosterols and anthocyanins. The fruit had 15.5% moisture contents seed and leaf had 8.5% each and stem and root bark had 9.5% each. The values of total ash were 7.0, 6.0, 4.5, 8.25 and 11.75%; values of water soluble ash were 4.9, 3.5, 0.5, 4.2 and 6.75%, while the values of acid insoluble ash 1.5, 1.75, 4.0, 3.75 and 4.25% in fruit pulp, leaf, stem bark, root bark and seeds, respectively. The fixed oil yield of M. buxifolia was measured to be 8.33, 10.62 and 0.56% in fruit pulp, seeds and leaves, respectively. Palmitic acid, Oleic acid, Linolenic acid, Stearic acid and Myristic acid were the most frequently found fatty acids in each part. The plant is a rich source of phosphorus, nitrogen and potassium. The plant contained safe amounts of tested trace elements as directed by WHO except for cobalt in root bark (10.7±0.01) and lead in stem bark (22.48±0.33).